2019
DOI: 10.1016/bs.abl.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

The role of membrane vesiculation and encapsulation in cancer diagnosis and therapy

Abstract: Introduction 160 2. Extracellular vesicles as diagnostic biomarkers for cancer 161 2.1 The fluid mosaic model of the membrane 164 2.2 Anisotropic orientational ordering and topological defects 165 2.3 Theoretical modeling of membrane vesiculation 166 3. Biocompatible nanostructured materials for cancer diagnostic and therapy 173 3.1 Photoactive nanoparticles for cancer treatment applications 174 4. Nanoparticle encapsulation 185 4.1 Monte Carlo simulations of particle encapsulation 186 5. Conclusions 189 Ackno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 164 publications
(199 reference statements)
0
4
0
Order By: Relevance
“…The spherical vesicle at the tip of the nanotube is assumed to be stabilized by isotropic nanodomains characterized by positive (convex) curvature, while the nanotube is assumed to be formed from anisotropic cylindrical curvature-preferring membrane constituents or nanodomains (C 1m > 0, C 2m = 0). This can lead to the detachment of the tip vesicle into an extracellular vesicle [74]. Shapes with an up-down symmetry are stable only at lower values of the reduced volume [67].…”
Section: Membrane Protrusions Coupled With Local Curvature Changesmentioning
confidence: 99%
“…The spherical vesicle at the tip of the nanotube is assumed to be stabilized by isotropic nanodomains characterized by positive (convex) curvature, while the nanotube is assumed to be formed from anisotropic cylindrical curvature-preferring membrane constituents or nanodomains (C 1m > 0, C 2m = 0). This can lead to the detachment of the tip vesicle into an extracellular vesicle [74]. Shapes with an up-down symmetry are stable only at lower values of the reduced volume [67].…”
Section: Membrane Protrusions Coupled With Local Curvature Changesmentioning
confidence: 99%
“…Upon additionally treating the electrochemically anodised TiO 2 NTs with oxygen plasma, surface contaminants are removed and an increase in oxygen content is observed. These oxygen plasma-treated NTs have beneficial effects on proliferation and adhesion of MG-63 cells [87]. It was also reported that oxygen plasma treatment also induces crystallisation of TiO 2 NTs from amorphous phase to rutile and/or anatase crystal structure.…”
Section: Additional Treatmentsmentioning
confidence: 89%
“…4E, left). This may cause the tip vesicle to separate and become an extracellular vesicle [87] (Fig. 4E, left).…”
Section: Anisotropic Membrane Components Modelsmentioning
confidence: 99%
“…with d i the effective diameter of species i. Ions with a high degree of solvation such as Li + have a large effective size; weakly solvated ions like Cs + have a small effective size. Drab et al [32] inferred from bulk permittivity data that g AM þ g X � 7:5 for NaCl electrolytes.…”
Section: Experimental Methodsmentioning
confidence: 99%